Quarterly GDP estimates for the German states - Robert Lehmann; Ida Wikman (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
To date, only annual information on economic activity is published for the 16 German states. In this paper, we calculate quarterly regional GDP estimates for the period between 1995 to 2020, thereby improving the regional database in Germany. The new data set will regularly be updated when quarterly economic growth for Germany becomes available. We use the new data for an in-depth business cycle analysis and find large heterogeneities in the duration and amplitudes of state-specific business cycles as well as in the degrees of cyclical concordance.
Keywords: C32; C53; E32; R11; 330; regional economic activity; mixed-frequency vectorautoregression; regional business cycles; concordance; Bayesian methods